2019
DOI: 10.1088/1361-665x/aaf20e
|View full text |Cite
|
Sign up to set email alerts
|

Demagnetizing field in single crystal ferromagnetic shape memory alloys

Abstract: Ferromagnetic materials, including ferromagnetic shape memory alloys (FSMAs or MSMAs), are subject to demagnetization. Because of this demagnetization, the MSMA literature is inconsistent with regards to where the applied magnetic field should be measured experimentally. In addition, many researchers assume a constant demagnetization factor when modeling MSMAs, but there has been little analysis to determine the accuracy of that assumption. In this work, we use finite element (FE) simulations to determine (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…First, the Guiel et al experiments were strain-controlled while the model is stress controlled. Next, the field was measured at the surface in these tests, which accordingly to Eberle et al [22] should not be used as the input applied field. Finally, the Guiel et al experiments, which were performed at 15 Hz frequency showed evidence that inertial effects were evident (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the Guiel et al experiments were strain-controlled while the model is stress controlled. Next, the field was measured at the surface in these tests, which accordingly to Eberle et al [22] should not be used as the input applied field. Finally, the Guiel et al experiments, which were performed at 15 Hz frequency showed evidence that inertial effects were evident (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…where H is the internal magnetic field experienced by the MSMA specimen, H app is the external magnetic field applied on the specimen, D is the demagnetization tensor [22].…”
Section: Model Derivationmentioning
confidence: 99%